The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/nu12040958
|View full text |Cite
|
Sign up to set email alerts
|

The Power of Packaging: A Scoping Review and Assessment of Child-Targeted Food Packaging

Abstract: Child-targeted food marketing is a significant public health concern, prompting calls for its regulation. Product packaging is a powerful form of food marketing aimed at children, yet no published studies examine the range of literature on the topic or the “power” of its marketing techniques. This study attempts such a task. Providing a systematic scoping review of the literature on child-targeted food packaging, we assesses the nutritional profile of these foods, the types of foods examined, and the creative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 63 publications
4
45
0
2
Order By: Relevance
“…For each product, we gathered images of the front and the back of the package. Besides the information described in Figure 1, we also categorized other packaging elements, such as the presence of children-oriented design (e.g., cartoon characters, cartoonish fonts, see also [11,20]) and traffic light labeling in the front of the package, as well as the list of ingredients.…”
Section: Products Description and Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…For each product, we gathered images of the front and the back of the package. Besides the information described in Figure 1, we also categorized other packaging elements, such as the presence of children-oriented design (e.g., cartoon characters, cartoonish fonts, see also [11,20]) and traffic light labeling in the front of the package, as well as the list of ingredients.…”
Section: Products Description and Data Collectionmentioning
confidence: 99%
“…see also [11,20]) and traffic light labeling in the front of the package, as well as the list of ingredients.…”
Section: Products Description and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review by Elliott and Truman (2020) showed that the vast majority of the products targeted at children available in the market cannot be regarded as suitable for them due to their high energy density and added sugar and fat. Sugar has been reported to be the most common nutrient exceeding nutritional recommendations among products targeted at children.…”
Section: Foods Targeted At Children: Why Do They Have So Much Sugar?mentioning
confidence: 99%
“…Nowadays, products with high sugar content targeted at children can be found across a wide range of food categories, including confectionary, cookies, dairy products, cereals and sweetened beverages (Elliott & Truman, 2020). Products are targeted at children through packaging and are also frequently formulated specifically for them; the problem is that such products are not actually healthier.…”
Section: Foods Targeted At Children: Why Do They Have So Much Sugar?mentioning
confidence: 99%